Plantar pressure-based temporal analysis of gait disturbance in idiopathic normal pressure hydrocephalus: Indications from a pilot longitudinal study. (April 2022) - Sun, Yubo; Liang, Siquan; Yu, Yang; Yang, Yuchen; Lu, Jiewei; Wu, Jingchao; Cheng, Yuanyuan; Wang, Yue; Wu, Jialing; Han, Jianda; Yu, Ningbo
Highlights: Idiopathic normal pressure hydrocephalus is a reversible degenerative brain disease and urgently needs diagnosis methods. Plantar pressure fundamentally signifies iNPH gait disturbance, and a temporal analysis method was proposed. An index calculated by DBA and DTW characterizes temporal variation of plantar pressure over walking cycles. Experiments with iNPH patients over CSF-TT and surgery follow-up well validated the proposed method and index. Abstract: Background and Objective: Idiopathic normal pressure hydrocephalus (iNPH) is a common yet potentially reversible neurodegenerative disease, and gait disturbance is a major symptom. Lots of methodological and clinical work has been conducted on gait disturbance analysis for differential diagnosis, presurgical test, and postsurgery assessment of iNPH. Nevertheless, the verification analysis was mostly lacking for surgery response, and the temporal characteristics of ground reaction force has been rarely investigated. Methods: In this work, we propose that plantar pressure features fundamentally signifies iNPH gait disturbance and improvement after cerebrospinal fluid (CSF) drainage by lumbar puncture tap test as well as surgical shunt implantation. The plantar pressure signals of six iNPH patients and eight healthy controls were collected, and an online database of sixteen healthy controls were used. For patients, data were collected in five periods, which are the baseline before the tap test, 8, 24, and 72 hours after the tap test, and one month after the shunt implantation surgery, respectively. Fast dynamic time warping (DTW) with an improved DTW barycenter averaging (DBA) method was proposed for temporal analysis with the measured and online plantar pressure data. An plantar-pressure variation index ( PPVI ) was formulated to characterize the temporal dynamic stability of walking. Results: The PPVI based on temporal analysis of plantar pressure well discriminated the impaired gait (baseline, 24 and 72 hours after tap test) with the improved gait (8 hours after tap test and follow up after surgery) of the patients. Further, the PPVI was close for the improved gait of the patients and the healthy gait measured in our study as well as in the online database. Conclusions: Plantar pressure-based temporal features are promisingly effective for clinical examination and treatment of iNPH.